2019
DOI: 10.3390/app9091835
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Observation of Adhesion Behavior During Ultrasonic Al Ribbon Bonding

Abstract: In-situ observation was performed on a transparent silica substrate during ultrasonic Al ribbon bonding, using a high-speed video camera with differing frame rates, 10 4 fps and 10 3 fps, to clarify the adhesion behavior. The bonding process was observed as follows. Initially, friction slip occurred, producing multiple island streaks in the direction parallel to the ultrasonic vibration. The island streaks were formed as a scratch, due to surface waviness of the Al ribbon. Momentarily, a belt-shaped bond zone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 49 publications
(147 reference statements)
0
1
0
Order By: Relevance
“…Ultrasonic bonding is widely used in industrial fields; however, there are still many unresolved phenomena. Takahashi et al directly observed the interfacial adhesion behavior during ultrasonic bonding between an Al ribbon and transparent silica substrate using a high-speed video camera with differing frame rates [27]. Initially, friction slip occurred, producing multiple island streaks in the direction parallel to the ultrasonic vibration.…”
Section: Innovative Processing On Micro/nanojoiningmentioning
confidence: 99%
“…Ultrasonic bonding is widely used in industrial fields; however, there are still many unresolved phenomena. Takahashi et al directly observed the interfacial adhesion behavior during ultrasonic bonding between an Al ribbon and transparent silica substrate using a high-speed video camera with differing frame rates [27]. Initially, friction slip occurred, producing multiple island streaks in the direction parallel to the ultrasonic vibration.…”
Section: Innovative Processing On Micro/nanojoiningmentioning
confidence: 99%